Thermo-responsive cell culture carrier: Effects on macrophage functionality and detachment efficiency. (24th August 2017) - Rennert, Knut; Nitschke, Mirko; Wallert, Maria; Keune, Natalie; Raasch, Martin; Lorkowski, Stefan; Mosig, Alexander S
Harvesting cultivated macrophages for tissue engineering purposes by enzymatic digestion of cell adhesion molecules can potentially result in unintended activation, altered function, or behavior of these cells. Thermo-responsive polymer is a promising tool that allows for gentle macrophage detachment without artificial activation prior to subculture within engineered tissue constructs. We therefore characterized different species of thermo-responsive polymers for their suitability as cell substrate and to mediate gentle macrophage detachment by temperature shift. Primary human monocyte- and THP-1-derived macrophages were cultured on thermo-responsive polymers and characterized for phagocytosis and cytokine secretion in response to lipopolysaccharide stimulation. We found that both cell types differentially respond in dependence of culture and stimulation on thermo-responsive polymers. In contrast to THP-1 macrophages, primary monocyte–derived macrophages showed no signs of impaired viability, artificial activation, or altered functionality due to culture on thermo-responsive polymers compared to conventional cell culture. Our study demonstrates that along with commercially available UpCell carriers, two other thermo-responsive polymers based on poly(vinyl methyl ether) blends are attractive candidates for differentiation and gentle detachment of primary monocyte–derived macrophages. In summary, we observed similar functionality and viability of primary monocyte–derived macrophages cultured on thermo-responsive polymers compared to standard cell culture surfaces. While this first generation of custom-made thermo-responsive polymers does not yet outperform standard culture approaches, our results are very promising and provide the basis for exploiting the unique advantages offered by custom-made thermo-responsive polymers to further improve macrophage culture and recovery in the future, including the covalent binding of signaling molecules and the reduction of centrifugation and washing steps. Optimizing these and other benefits of thermo-responsive polymers could greatly improve the culture of macrophages for tissue engineering applications.